Case Report: Immune Checkpoint Inhibitors Successfully Controlled Asymptomatic Brain Metastasis in Esophageal Squamous Cell Carcinoma - Xiao, Linlin; Lin, Chi; Liu, Yueping; Wu, Yajing; Wang, Jun (Frontiers in Immunology, 2022)
Background Brain metastases are the most common cause of intracranial malignancy, often resulting in significant morbidity and mortality. Brain metastases from esophageal squamous cell carcinoma (ESCC) are relatively rare, with a rate of generally less than 2%. Case report In this article, we report a rare case of ESCC with asymptomatic brain metastasis. The combined positive score (CPS) of programmed cell death ligand 1 (PD-L1) from the primary tumor was 2 by DAKO 22C3 and 3 by VENTANA SP263. The proportion of tumor infiltrating lymphocytes (TILs) was 1%. After receiving 15 cycles of immune checkpoint inhibitors (ICIs), the patient’s brain metastatic lesion had disappeared and was replaced by a local necrotic area. He retains good cognitive function with a stable disease at the primary site. Conclusions This is the first to be reported in an ESCC patient whose brain metastatic lesion had a complete response to ICIs, which may provide supporting data for using ICIs as an option of treatment for ESCC patients with brain metastases.